Design and mechanisms of antifouling materials for surface plasmon resonance sensors. (August 2016) - Liu, Boshi; Liu, Xia; Shi, Se; Huang, Renliang; Su, Rongxin; Qi, Wei; He, Zhimin
Graphical abstract: Abstract: Surface plasmon resonance (SPR) biosensors have many possible applications, but are limited by sensor chip surface fouling, which blocks immobilization and specific binding by the recognizer elements. Therefore, there is a pressing need for the development of antifouling surfaces. In this paper, the mechanisms of antifouling materials were firstly discussed, including both theories (hydration and steric hindrance) and factors influencing antifouling effects (molecular structures and self-assembled monolayer (SAM) architectures, surface charges, molecular hydrophilicity, and grafting thickness and density). Then, the most recent advances in antifouling materials applied on SPR biosensors were systematically reviewed, together with the grafting strategies, antifouling capacity, as well as their merits and demerits. These materials included, but not limited to, zwitterionic compounds, polyethylene glycol-based, and polysaccharide-based materials. Finally, the prospective research directions in the development of SPR antifouling materials were discussed. Statement of Significance: Surface plasmon resonance (SPR) is a powerful tool in monitoring biomolecular interactions. The principle of SPR biosensors is the conversion of refractive index change caused by molecular binding into resonant spectral shifts. However, the fouling on the surface of SPR gold chips is ubiquitous and troublesome. It limits the application of SPR biosensors by blocking recognition element immobilization and specific binding. Hence, we write this paper to review the antifouling mechanisms and the recent advances of the design of antifouling materials that can improve the accuracy and sensitivity of SPR biosensors. To our knowledge, this is the first review focusing on the antifouling materials that were applied or had potential to be applied on SPR biosensors.